2011
DOI: 10.1111/j.1442-9071.2010.02425.x
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset persistent Descemet's membrane detachment following uncomplicated clear corneal incision cataract surgery

Abstract: We report the case of a 76-year-old man who developed a late-onset Descemet's membrane detachment (DMD) 5 months after uncomplicated cataract surgery. Despite two air tamponade procedures that initially appeared successful, the DMD continued to return. After careful examination it was found that a surgical entry wound may have been scarred open (fish-mouthing), which continually promoted Descemet's membrane to detach. Excision of the abnormal scar led to an almost complete resolution of the DMD. To our knowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“… 12 DMD has also been reported in Descemet membrane endothelial keratoplasty and deep anterior lamellar keratoplasty. 13 , 14 Several mechanisms have been implicated in the etiology of DMD, such as a shallow anterior chamber, 1 use of blunt microkeratomes, 15 shelved and/or anteriorly placed incisions, 16 , 17 engagement of the DM during intraocular lens implantation, 18 the inadvertent injection of saline into the space between the deep stroma and the DM. 12 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 12 DMD has also been reported in Descemet membrane endothelial keratoplasty and deep anterior lamellar keratoplasty. 13 , 14 Several mechanisms have been implicated in the etiology of DMD, such as a shallow anterior chamber, 1 use of blunt microkeratomes, 15 shelved and/or anteriorly placed incisions, 16 , 17 engagement of the DM during intraocular lens implantation, 18 the inadvertent injection of saline into the space between the deep stroma and the DM. 12 …”
Section: Discussionmentioning
confidence: 99%
“…Descemet’s membrane detachment (DMD) is often attributable to cataract surgery. 1 3 Various types of DMD can cause corneal endothelial dysfunction. In 1928, DMD was first described by Samuels; 4 he reported three patients with DMD after iridectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Wong et al reported a case of a patient who developed a Descemet’s detachment 8 months after THC:YAG (thulium, holmium, chromium-doped yttrium aluminum garnet crystal) laser sclerostomy 1. Stewart et al reported a case of a Descemet’s detachment that occurred 5 months after uncomplicated cataract surgery 2. To our knowledge, this is the first report of delayed Descemet’s tear and detachment occurring 11 months after cataract surgery.…”
Section: Introductionmentioning
confidence: 91%
“…3 [1]. Postoperative Descemet-Membran-Ablösungen treten am häufigsten nach Kataraktoperationen auf [9,11,12,15], sind aber auch nach Trabekulektomien [23], Iridektomien [9] und Pars-plana-Vitrektomien [10] beschrieben [1] [3,7,16,20]. Als ein wichtiges Anzeichen wird hier ein Stromaödem am ersten post-operativen Tag beschrieben [21,22].…”
Section: Diskussionunclassified